Improved Fe2O3/Al2O3 Systems for the Oxidation of a Model Organic Pollutant Using H2O2 as Oxidant - Di Luca, Carla (2014)
Different Fe2O3/Al2O3 catalysts (4 wt% Fe) were prepared and characterized by N2 physisorption, SEM-EDX, TGA and XRD. The systems were tested for the oxidation of high concentration phenol solutions (5 g/L) in a batch reactor at 50 ºC, using H2O2 as oxidant. In order to enhance the catalyst stability two strategies were combined: an elevated temperature of calcination (900 °C) and pre-treatments with different organic acids (acetic, oxalic acid). The stability of the catalyst was improved significantly (leaching levels were reduced by up to 70%), with a good performance over the global oxidation process: mineralization levels of ca. 50% with oxidant consumption efficiencies of around 75%.